Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini) - Ruiz, Gustavo R.s.; Sobrinho, Adriana T. (Zootaxa, 2016)
Four syntopic species of Soesilarishius Makhan, 2007 are recorded from the Floresta Estadual do Trombetas, Oriximiná, Pará, Brazil. The first is the type species of the genus, S. amrishi Makhan, 2007, of which we redescribe the male and describe the female for the first time. The other three species are new and described herein based on both sexes: S. laticlavus sp. nov., S. trombetas sp. nov. and S. elongatulus sp. nov.